The Impact of PJBL (Project Based Learning) Model On Grade Iv Students’ Arts, Culture, and Crafraftsmanship Learning Outcomes - Wahyuningtyas, Deni Setiawan, Sri (Universitas Negeri Semarang, 2018)
The research aimed to examine the effect of PJBL model (Project Based Learning) on learning outcome at SBdP at the fourth grade student of SDN Jepang 05 Kudus. The design of the research was quasi-experimental with noquivalent control group design. The population of the research was fourth grade student of SDN Jepang 05 Kudus 2016/2017. The sample collection techniques used Nonprobability Sampling with saturated sampling technique. The amount of the sample were 25 students for experiment class and 23 students the control class. The data collection techniques used test, observation, and documentation. The data analysis employed: normality test, homogeneity, average difference test and N-Gain test. The results of the research showed that t test obtained t calculation of 0.000 <0,05 so that Ha accepted and Ho rejected. This indicates that used PjBL model has significant influence on student activity and learning outcome at SBdP which has been also proven through the control class gain index of 0.399 (Medium), and the experimental class gain index of 0.701 (High). Student activity of experiment class was higher than control class. The research concluded that the use of Project Based Learning model gave a significant difference of influence on the activity and the student’s learning outcome on the material making the leaf bone craft in SBdP learning.